Multiculturalism and inconsistency in the perception of sex education in Australian society - Almahbobi, Ghanim (Australasian Medical Journal Pty Ltd, 2012)
A group of individuals who share common beliefs form a culture in which they communicate their values and attributes about certain aspects of society. Sex education remains one of the early teachings that humans experience irrespective of the race or level of development of a given society. However, different cultures perceive sex education differently due to differences in attitudes and beliefs, leading to significant diversity in the management of sex education among different societies across the globe. Many studies have found that in a traditional society with a homogeneous culture, the foremost reason for the different approaches to sex education is related to traditional values, in addition to other factors such as religion and political belief. In order to improve sex education, and consequently, sexual health in a modern multicultural society such as Australia, it becomes imperative to identify the inconsistency in beliefs about sex education among individuals with different cultural backgrounds in the Australian population. In this report, the author highlights similarities and differences in the methods employed by certain cultures of the Australian population. The report considers the different cultural environments of specific societies, the prevalence of sex education in these societies and how culture influences the prevalence. The concluding thoughts reflect on the success of the education programs in Australia, based on the idea that resolving the problems of sex education needs support from a number of bodies within Australian society.